Mulheres negras em jornais: uma análise interseccional dos periódicos O Povo e Diário Do Nordeste (2003 a 2020 em Fortaleza-CE) - Sales, Suewellyn Cassimiro (2023)
Newspapers, along with dominant institutions such as School, the State and the Church, have the power to define social values and influence ideas, including the status of black women (Collins, 2019). Based on this reflection, the general objective of this work is to study how black women are represented in the newspapers O Povo and Diário do Nordeste, the objects of this research, the main media outlets and most widely circulated periodicals in the city of Fortaleza, capital of Ceará. The specific objectives are: 1. To identify Controlling Images – mammy; matriarch; mother dependent on the state; welfare queen; black lady; jezebel, prostitute or hoochie; modern mammy; and pretty baby (Collins, 2019; Bueno, 2020) – and intersectional oppressions; 2. Identify new categories; and 3. Interpret the corpus, texts from O Povo and Diário do Nordeste, signed by the editorial staff, from 2003 to 2020, the result of exploratory research with the descriptors “mulher negra” and “mulheres negras” in the search tools of their respective portals. The methodologies applied are Content Analysis by Laurence Bardin (1977) and Intersectional Roulette by Fernanda Carrera (2021). I also adopt Conceição Evaristo’s (2008) notion of escrevivência as a way of inserting myself into the text, mixing life experiences with social events. The theoretical framework draws on black feminist thinkers such as Lélia Gonzalez (1984), Djamila Ribeiro (2017, 2019), Patricia Hill Collins (2019), Winnie Bueno (2020) and Carla Akotirene (2021), using the notions of Controlling Images, intersectionality and lugar de fala. As a result, I identified in the corpus: all the images of control, with a predominant recurrence of the black lady, the matriarch and the mammy, in this sequence; the reproduction of the intersectional oppressions of classism, racism, sexism and xenophobia, in this order; two new categories: hastes iluminadas and intersectional oppressions, thought up from the Intersectional Roulette; the absence of illumination of the disability and weight stems; confirmation of the hypotheses, which dialogue with the identification of the predominant images of control; and linearity in the discourse on black women, which repeatedly represents us as poor, exploited people – Controlling Images of the matriarch and mammy – or as women who are constantly but slowly advancing socially, from a discourse of overcoming – controlling image of the black lady. Finally, I believe that the objects of research, in the journalistic narratives of the corpus, contributed little to overcoming the inequalities faced by black women and reproduced negative content about us